Optimization of Counseling Guidance by Bhabinkamtibmas in the Criminal Act of Assault in the Jurisdiction of Nganjuk Police Region - Sitanggang, Juan Patrick Leonardo; Fahrurrozi, Moch.; Farhan, Lazuardhy; Boseke, Timothy Torro (Tanggon Kosala, 2025)
This research aims to describe the phenomenon of mobbing, explain the role of extension guidance activities by Bhabinkamtibmas, identify factors that influence extension guidance activities, and examine relevant theories and concepts to optimize extension guidance activities. This research uses a qualitative approach with field research methods. Data analysis by data reduction, data presentation, and concluding. The results of the research show that cases of beatings in the last 3 years still have a tendency to increase, so the role of Bhabinkamtibmas through counseling and guidance activities is expected to reduce the number of cases of pre-emptive beatings that occur in the jurisdiction of the Nganjuk Police. This research examines the application of Management theory with elements of POAC and 6M and SWOT analysis based on factual conditions, including information from intelligence regarding problems, rules, and regulations related to activities, organizational resources, and internal-external factors.